2014
DOI: 10.4319/lo.2014.59.4.1275
|View full text |Cite
|
Sign up to set email alerts
|

Tracing carbon flow from microphytobenthos to major bacterial groups in an intertidal marine sediment by using an in situ 13C pulse‐chase method

Abstract: Carbon flow from benthic diatoms to heterotrophic bacterial was traced in an intertidal sediment for 5 consecutive days. 13 C-labeled bicarbonate was sprayed onto the sediment surface during low tide and 13 C-label incorporation in major carbon pools, intermediate metabolites, and biomarkers were monitored. Phospholipidderived fatty acid (PLFA) and ribosomal ribonucleic acid (rRNA) were used to identify the responsible members of the microbial community at class and family phylogenetic resolution. Diatoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 53 publications
(87 reference statements)
2
32
0
Order By: Relevance
“…There was rapid transfer of carbon from MPB to bacteria and fauna as evidenced by the detection of 13 C in these compartments within 0.5 d of label application. Rapid transfer of fixed carbon from MPB to heterotrophic bacteria and fauna is attributable to the release of low molecular weight compounds (within 0.5 d; Miyatake et al ) and extracellular polysaccharides (1–3 d; Miyatake et al ) by MPB. However, the amount of MPB‐C transferred to bacteria and fauna was limited, representing only ≤7.8% of the initially incorporated 13 C and ≤16.5% of the 13 C remaining within sediment OC at any time during the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was rapid transfer of carbon from MPB to bacteria and fauna as evidenced by the detection of 13 C in these compartments within 0.5 d of label application. Rapid transfer of fixed carbon from MPB to heterotrophic bacteria and fauna is attributable to the release of low molecular weight compounds (within 0.5 d; Miyatake et al ) and extracellular polysaccharides (1–3 d; Miyatake et al ) by MPB. However, the amount of MPB‐C transferred to bacteria and fauna was limited, representing only ≤7.8% of the initially incorporated 13 C and ≤16.5% of the 13 C remaining within sediment OC at any time during the study.…”
Section: Discussionmentioning
confidence: 99%
“…Given their high productivity and their location at the land-sea interface, MPB may play a crucial role in determining the quantity and form of carbon available to coastal ecosystems and transported to the more open ocean. Up to 75% of MPB production can be exuded as extracellular organic carbon (EOC) (Goto et al 2001) which, along with MPB, can contribute significantly to the carbon requirements of bacteria (Bellinger et al 2009;Oakes et al 2010b;Hardison et al 2011;Miyatake et al 2014) and higher heterotrophs (Middelburg et al 2000;Oakes et al 2010a;Evrard et al 2012). MPBderived carbon (MPB-C) may ultimately be removed from sediment via resuspension (de Jonge and van Beusekom 1995), grazing, or fluxes of dissolved organic carbon (DOC) and dissolved inorganic carbon (DIC) from inundated sediments (Evrard et al 2012;Oakes et al 2012;Oakes and Eyre 2014), or CO 2 from exposed sediments (Oakes and Eyre 2014), following respiration and/or bacterial and virally-mediated degradation (Glud and Middelboe 2004).…”
mentioning
confidence: 99%
“…A similar carbon transfer was found in a freshwater chemoautotrophic benthic community, although, in this case the consumers were more diverse and seemed to have a higher specialization (Coskun et al ., ). These differences may be attributed to the method, which was fundamentally different from the one used by Miyatake and colleagues (). The latter authors also showed that only the water‐extractable EPS was consumed.…”
Section: The Role and Fate Of Eps In Benthic Phototrophic Communitiesmentioning
confidence: 91%
“…Addition of glucose to such biofilm causes shifts in the community composition and breaks down the coupling between algae and bacteria. Miyatake and colleagues () showed that part of the carbon exuded by the diatoms was consumed by Gammaproteobacteria, Bacteroidetes and Deltaproteobacteria, which represented 21%, 8% and 7% of the 16S rRNA clone libraries in this diatom biofilm. These groups equally consumed organic matter produced by the diatoms.…”
Section: The Role and Fate Of Eps In Benthic Phototrophic Communitiesmentioning
confidence: 99%
“…The development of a new compound‐specific stable isotope technique enabled the unraveling of metabolic pathways of photosynthetically acquired carbon in benthic diatoms (Moerdijk‐Poortvliet et al ). Liquid Chromatography Isotope Ratio Mass Spectrometry (LC/IRMS) was applied to study CHO metabolism in diatom mats by Oakes et al () and by Miyatake et al (). The development of additional LC/IRMS methods for AAs and nucleic acids allows the study of all major classes of biological compounds, which improved our insight in the functioning of diatom mats (Boschker et al ; Moerdijk‐Poortvliet et al ,).…”
mentioning
confidence: 99%